Theoretical and Mathematical Foundations of Computer Science Second International Conference, ICTMF 2011, Singapore, May 5-6, 2011. Selected Papers - Zhou, Qihai; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed post-proceedings of the Second International Conference on Theoretical and Mathematical Foundations of Computer Science, ICTMF 2011, held in Singapore in May 2011. The conference was held together with the Second International Conference on High Performance Networking, Computing, and Communication systems, ICHCC 2011, which proceedings are published in CCIS 163. The 84 revised selected papers presented were carefully reviewed and selected for inclusion in the book. The topics covered range from computational science, engineering and technology to digital signal processing, and computational biology to game theory, and other related topics.
Keywords: Computer science; Computer Communication Networks; Data structures (Computer science).; Information systems; Computer vision; Computer Science; Mathematics of Computing; Data Structures, Cryptology and Information Theory; Information Systems and Communication Service; Computer Communication Networks; Computer Imaging, Vision, Pattern Recognition and Graphics